CAN WE MAKE THE ―NEW URBAN AGENDA‖ MORE AGE- FRIENDLY FOR ISLAND-BASED OLDER PEOPLE’S HOUSING? A CASE STUDY OF XINZHOU TOWN, CHINA - Qiaowei Yang (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2016)
The paper uses the “New Urban Agenda” and the “Age-friendly Cities” as research framework, to investigate housing for island-based older people living in one developing area of China. The results identify that local older residents are facing: difficulties in getting modifications and maintenance because of the younger generations’ migration and local industrial development, poor affordability of care home living, as well as poor transport links that prevent access to housing services. These issues are caused by the “urban-rural linkages” as well as “urbanization”, which are important points in the “New Urban Agenda”.Based on the findings, the author argues that future actions need to be done to make the implementation of the “New Urban Agenda” more age-friendly.